Alienability splits in Swedish from a diachronic perspective - Piotrowska, Alicja; Skrzypek, Dominika (Penerbit Universiti Kebangsaan Malaysia, 2022)
The paper discusses possessive expressions with body-part nouns in Swedish (1300–1550) with particular focus on the so-called alienability splits, i.e., separate patterns of marking possession for alienable and inalienable entities. The key problem to be addressed is to what extent such splits can be found in Swedish and the aim of the study is to establish when they arise and what motivates their formation. The inalienable possessive constructions with bodypart referents in Modern Swedish include the so-called implicit possession, where only the definite article is used and the inalienable prepositional construction of the type ‘the head on him’. The analyzed material consists of Old Swedish prosaic texts written between 1300 and 1550. The corpus includes eight texts and amounts to ca. 250,000 words. The material is studied both quantitatively and qualitatively; collostructional analysis is used for the statistical overview of the data. The results of the collostructional analysis confirm that the implicit possessive construction first appears in Period II (1350–1450) and becomes grammaticalized in the late 1400s. The inalienable prepositional construction is not found in the material studied and thus must be of later origin. The results suggest further that the inalienable possessive constructions do not arise as a result of the speaker’s wish to disambiguate the notion of inalienability but are a by-product of other diachronic processes, such as the grammaticalization of the definite article in the indirect anaphoric context.